Unaffected carrier males in families with fragile X syndrome. - Howard-Peebles, P N (1985)
Males who transmit the fragile X chromosome but are themselves clinically normal have occasionally been observed. We have studied three families segregating the fragile X. In one family, there are three unaffected carrier males, and in each of the other two families, there is one unaffected carrier male. Three of these carrier males were studied cytogenetically, and none exhibited the fra(X)(q27) marker. The occurrence of carrier males and of other unusual genetic features in fragile X families suggest that this condition is not inherited as a standard recessive trait linked to the X chromosome.